Sections 2-2

Solve the following equations with the given initial conditions:

1. y ' - 2 y = 0, y(1)= - 3

****

p(t)=-2

P(t)=-2t

=e^(2t)

y(1)=-3 so C=-3

y=Ce^(-P(t))

y=-3e^(2t)

#$&*

2. t^2 y ' - 9 y = 0, y(1) = 2.

****

y’-(9/t^2)y=0

p(t)=(-9/t^2)

P(t)=(9/t)

y(1)=C so C=2

=2e^(-9/t)

@& & y(t) = C e^(9 / t), so

y(1) = C e^(9/1) = C e^9,

y(1) = 1 so C e^9 = 1 and C = 1 / e^9 = e^-9.

The solution is

y(t) = e^-9 * e^(9/t),

or

y(t) = e^(9 / t - 9),

which could be expressed as

y(t) = e^( 9 ( 1/t - 1) ).*@

#$&*

3. (t^2 + t) y' + (2t + 1) y = 0, y(0) = 1.

****

I don’t know if you do the same process as the y(1) problems, but that’s what I did:

y’+[(2t+1)/(t^2+t)]y=0

y’+(3/t^2)y=0

p(t)=(3/t^2)

P(t)=(-3/t)

y(0)=C so C=1

=1e^(3/t)

@& Dividing through by t^2 + t you get

y ' + (2 t + 1) / (t^2 + t) y = 0.

p(t) = (2 t + 1) / (t^2 + t),

so you have to integrate p(t).

The substitution u = t^2 + t yields du = 2 t + 1, so the integral becomes

integral(du / u),

which is equal to ln | u | .

Substituting t^2 + t for u we get

ln (t^2 + t).

Now e^(-integral ( p(t) ) ) = e^- (ln ( t^2 + t) = 1 / (t^2 + t), so the solution is

y = c * 1 / (t^2 + t) = c / (t^2 + t).*@

#$&*

4. y ' + sin(3 t) y = 0, y(0) = 2.

****

p(t)=sin(3t)

P(t)=[-cos(3t)/3]

y(0)=C so C=2

=2e^(cos(3t)/3)

@& The solution is

y(t) = C e^(-cos(t)).

y(0) = C e^(-cos(0 ) = C e^(-1) = C / e,

so

C / e = 1 and

C = e.

y(t) = e * e^(-cos(t) ) = = e^(-cos(t) + 1).*@

#$&*

5. Match each equation with one of the direction fields shown below, and explain why you chose as you did.

y ' - t^2 y = 0

****

Graph E, because on each of these, I found p(t) then integrated that to get P(t) and then put it in the exponential function, for example, then graphed each “y” function:

p(t)=(-t^2)

P(t)=(-t^3/3)

y=e^(t^3/3)

#$&*

y ' - y = 0

****

Graph A

p(t)=-1

P(t)=(-t)

y=e^(t)

#$&*

y' - y / t = 0

****

Graph C

p(t)=(-1/t)

P(t)=(-ln(abs (t)))

y=abs (t)

#$&*

y ' - t y = 0

****

Graph B

p(t)=(-t)

P(t)=(-t^2/2)

y=e^(t^2/2)

#$&*

y ' + t y = 0

****

Graph F

p(t)=t

P(t)=(t^2/2)

y=e^(-t^2/2)

#$&*

6. The graph of y ' + b y = 0 passes through the points (1, 2) and (3, 8). What is the value of b?

****

I graphed the points and connected them. I’m not sure how to go about solving this, but since p(t)=b would you integrate that and get P(t)=(b^2/2)?! How do I use my 2 points?!

@& The variable of integration is t, not b, so integrating b wouldn't give you b^2 / 2.

Your solution is y(t) = C e^(- b t).

Substituting we get the equations

1 = C e^(-b) and

8 = C e^(-3 b).

We solve these two simultaneous equations for C and b.

Dividing the second equation by the first we get

8 = e^(-2 b)

so that

-2 b = ln(8) and

b = -ln(8) / 2.

Substituting this into the first equation we get

1 = C e^(ln(8) / 2)

e^(ln(8) / 2) = e^(ln(8)) ^(1/2) = 8^(1/2) = sqrt(8) so

1 = C * sqrt(8) .

Therefore

C = 1 / sqrt(8) = 1 / (2 sqrt(2) ) = sqrt(2) / 4.

The solution is

y = (sqrt(2) / 4) e^(-ln(8) / 2 * t)

= sqrt(2) / 4 * (1/8) ^ ( t / 2).

*@

#$&*

7. The equation y ' - y = 2 is first-order linear, but is not homogeneous.

If we let w(t) = y(t) - 2, then:

What is w ' ?

What is y(t) in terms of w(t)?

What therefore is the equation y ' - y = 2, written in terms of the function w and its derivative w ' ?

Now solve the equation and check your solution:

Solve this new equation in terms of w.

Substitute y + 2 for w and get the solution in terms of y.

Check to be sure this function is indeed a solution to the equation.

****

If w(t)=y(t)+2

w’(t)=y’(t)+0

Solving for y(t): y(t)=w(t)-2

The equation y’-y=2 would be w(t)-(w(t)-2)=0

Is this a good start?!

@& Good start.

The substitution should have been w(t) = y(t) - 2.

With this substitution

w ' (t) = y ' (t) - 0 = y ' (t),

and

y(t) = w(t) + 2

so the equation

y ' - y = 2

becomes

w ' + w + 2 = 2, or just

w ' + w = 0.

The solution is w(t) = C e^(-t), so

y(t) = w(t) - 2 = C e^(-t) - 2.

You can substitute this into the original equation and see that it works.*@

#$&*

8. The graph below is a solution of the equation y ' - b y = 0 with initial condition y(0) = y_0. What are the values of y_0 and b?

****

p(t)=(-b)

mu(t)=e^(-b^2/2)

(e^(-b^2/2)*y’) – (e^(-b^2/2))=0

Would I integrate both sides wrt “b” then solve for y?

@& The variable of integration is t, not b.

The integral of -b with respect to t is - b t + c.

The solution that follows is

y = y0 e^( b t).

The y-intercerpt of this equation is y_0, and can be read from the graph of the solution.

y ' = b * y_0 e^(b t),

so the t = 0 slope of the graph is

y ' (0) = b * y_0.

Having observed the value of y_0 from the graph, you can estimate the slope at t = 0, set the result equal to b * y_0, and solve for b.*@

#$&*

self-critique #$&*

#$&* self-critique

self-critique rating

@& You need to go through the details of writing out the solution and substituting known values in order to evaluate constants.*@

@& See my other notes as well, and let me know if you have questions.*@